Suicidal and self-harm ideation among Chinese hospital staff during the COVID-19 pandemic: Prevalence and correlates. (February 2021) - Xu, Xiaoming; Wang, Wo; Chen, Jianmei; Ai, Ming; Shi, Lei; Wang, Lixia; Hong, Su; Zhang, Qi; Hu, Hua; Li, Xuemei; Cao, Jun; Lv, Zhen; et al.
Highlights: This was the first study on suicidal and self-harm ideation (SSI) in hospital staff during a public health crisis. 744 (6.47%) hospital staff reported a suicidal and self-harm ideation. The epidemic-related factors, the psychological status and need, and the perceived stress and support were associated with SSI in hospital staff. The current SSI in the initial phase of a pandemic might lower than that in non-pandemic days. Abstract: The COVID-19 pandemic put global medical systems under massive pressure for its uncertainty, severity, and persistence. For detecting the prevalence of suicidal and self-harm ideation (SSI) and its related risk factors among hospital staff during the COVID-19 pandemic, this cross-sectional study collected the sociodemographic data, epidemic-related information, the psychological status and need, and perceived stress and support from 11507 staff in 46 hospitals by an online survey from February 14 to March 2, 2020. The prevalence of SSI was 6.47%. Hospital staff with SSI had high family members or relatives infected number and the self-rated probability of infection. Additionally, they had more perceived stress, psychological need, and psychological impact. On the contrary, hospital staff without SSI reported high self-rated health, willingness to work in a COVID-19 ward, confidence in defeating COVID-19, and perceived support. Furthermore, they reported better marital or family relationship, longer sleep hours, and shorter work hours. The infection of family members or relatives, poor marital status, poor self-rated health, the current need for psychological intervention, perceived high stress, perceived low support, depression, and anxiety were independent factors to SSI. A systematic psychological intervention strategy during a public health crisis was needed for the hospital staff's mental well-being.